25÷5 mũ x=5 mũ x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(5\left(x+7\right)-10=2^3\cdot5\)
\(\Rightarrow5\left(x+7\right)-10=40\)
\(\Rightarrow5\left(x+7\right)=40+10\)
\(\Rightarrow x+7=\dfrac{50}{5}\)
\(\Rightarrow x+7=10\)
\(\Rightarrow x=10-7\)
\(\Rightarrow x=3\)
b) \(9x-2\cdot3^2=3^4\)
\(\Rightarrow9x-18=81\)
\(\Rightarrow9x=81+18\)
\(\Rightarrow9x=99\)
\(\Rightarrow x=\dfrac{99}{9}\)
\(\Rightarrow x=11\)
c) \(5^{25}\cdot5^{x-1}=5^{25}\)
\(\Rightarrow5^{x-1}=5^{25}:5^{25}\)
\(\Rightarrow5^{x-1}=1\)
\(\Rightarrow5^{x-1}=5^0\)
\(\Rightarrow x-1=0\)
\(\Rightarrow x=1\)
a) 5(�+7)−10=23⋅55(x+7)−10=23⋅5
⇒5(�+7)−10=40⇒5(x+7)−10=40
⇒5(�+7)=40+10⇒5(x+7)=40+10
⇒�+7=505⇒x+7=550
⇒�+7=10⇒x+7=10
⇒�=10−7⇒x=10−7
⇒�=3⇒x=3
b) 9�−2⋅32=349x−2⋅32=34
⇒9�−18=81⇒9x−18=81
⇒9�=81+18⇒9x=81+18
⇒9�=99⇒9x=99
⇒�=999⇒x=999
⇒�=11⇒x=11
c) 525⋅5�−1=525525⋅5x−1=525
⇒5�−1=525:525⇒5x−1=525:525
⇒5�−1=1⇒5x−1=1
⇒5�−1=50⇒5x−1=50
⇒�−1=0⇒x−1=0
⇒�=1⇒x=1
a) 25+x=0
x=0-25
x=-25
b)\(2^x:2^{19}=2^{25}\)
\(2^x=2^{25}.2^{19}\)
\(2^x=2^{44}\)
=>x=44
c)\(5^x.5^{18}=5^{54}\)
\(5^x=5^{54}:5^{18}\)
\(5^x=5^{36}\)
=>x=36
\(\left(x+1\right)^3=27\)
\(\left(x+1\right)^3=3^3\)
\(\Rightarrow x+1=3\)
\(x=2\)
\(\left(x+1\right)^3=27\)
\(< =>\left(x+1\right)^3=3.3.3=3^3\)
\(< =>x+1=3< =>x=3-1=2\)
\(\left(2x+3\right)^3=9.81\)
\(< =>\left(2x+3\right)^3=9.9.9\)
\(< =>\left(2x+3\right)^3=9^3\)
\(< =>2x+3=9< =>2x=6\)
\(< =>x=\frac{6}{2}=3\)
a, (-0,2)2 \(\times\) 5 - \(\dfrac{2^{13}\times27^3}{4^6\times9^5}\)
= 0,04 \(\times\) 5 - \(\dfrac{2^{13}\times3^9}{2^{12}\times3^{10}}\)
= 0,2 - \(\dfrac{2}{3}\)
= \(\dfrac{2}{10}\) - \(\dfrac{2}{3}\)
= - \(\dfrac{7}{15}\)
b, \(\dfrac{5^6+2^2.25^3+2^3.125^2}{26.5^6}\)
= \(\dfrac{5^6+4.5^6+8.5^6}{26.5^6}\)
= \(\dfrac{5^6.\left(1+4+8\right)}{26.5^6}\)
= \(\dfrac{1}{2}\)
a, (-0,2)2 ×× 5 - 213×27346×9546×95213×273
= 0,04 ×× 5 - 213×39212×310212×310213×39
= 0,2 - 2332
= 210102 - 2332
= - 715157
b, 56+22.253+23.125226.5626.5656+22.253+23.1252
= 56+4.56+8.5626.5626.5656+4.56+8.56
= 56.(1+4+8)26.5626.5656.(1+4+8)
= 1221
a) \(9.x-2.x=\frac{6^{27}}{6^{25}}+\frac{48}{12}\)
\(\Leftrightarrow7x=6^2+4\)
\(\Leftrightarrow7x=36+4=40\)
\(\Leftrightarrow x=\frac{40}{7}\)
Vậy : \(x=\frac{40}{7}\)
b) \(11^x=5.x+\frac{5^{31}}{5^{29}}+3.2^2-10^0\)
\(\Leftrightarrow11^x=5x+5^2+12-1\)
\(\Leftrightarrow11^x=5x+36\)
\(\Rightarrow x\in\varnothing\)
Bài 2:
a: \(\Leftrightarrow\left(x-5\right)\left(x+5\right)-\left(x+5\right)=0\)
=>(x+5)(x-6)=0
=>x=-5 hoặc x=6
b: \(\Leftrightarrow4x^2-4x+1-4x^2+1=0\)
=>-4x+2=0
hay x=1/2
c: \(\Leftrightarrow\left(x^2+4\right)\left(x^2-1\right)=0\)
=>x=1 hoặc x=-1
Bài 1:
2\(x\) = 4
2\(^x\) = 22
\(x=2\)
Vậy \(x=2\)
Bài 2:
2\(^x\) = 8
2\(^x\) = 23
\(x=3\)
Vậy \(x=3\)
Ta có : 25 : 5^x = 5^x
<=> 25 = 5^x . 5^x
<=> x = 1
Nhớ k mk nha !!